Support for age related firearm policies among Black American firearm owners: examining the role of children in the home - Vanya C. Jones; Elizabeth D. Wagner; Julie A. Ward; Rebecca Valek; Cassandra Crifasi (BMC Pediatrics)
Abstract Background In recent years, ownership of firearms has increased to approximately one-third of American households. Firearm access is a threat to child safety, with the most common location of fatal childhood firearm injury being at home. Exploring differences in opinions on gun violence prevention policies among Black firearm owners could inform community-supported interventions as one approach to reduce violent injuries among disproportionately affected youth. This study examined support for child-safety-related firearm policies among Black gun owners and whether support differed between those with and without children living in the home. Methods This observational cross-sectional study used data from the 2023 wave of the National Survey of Gun Policy, fielded using NORC’s AmeriSpeak Panel. Black survey respondents (n = 177) self-reported firearm ownership and whether children lived in the home. Fourteen key policies potentially relevant to youth firearm violence, firearm exposure, and safety were evaluated in this study using a binary measure of support derived from a five-point Likert scale. Survey weights were applied to adjust for sampling deviations, and survey-weighted proportions (WPs) and 95% confidence intervals (CIs) were calculated to examine differences between groups. Results Black firearm owners with children in the home (n = 65) were younger, had lower income, and were more likely to live in metropolitan areas compared to those without children in the home (n = 112). There was over 60% support, with little variance, among Black firearm owners with and without children living in the home for 11 of the 14 policies. The only significant difference among these groups was in support for temporary firearm removal by law enforcement for individuals posing an immediate threat. Although still over 60%, support was lower among owners with children living in the home (65%, CI: 0.51–0.79) compared to those without children living in the home (85%, CI: 0.77–0.93). Conclusions This study found that Black firearm owners are a demographically diverse group overall and when comparing those with and without children living in the home. These findings suggest that Black firearm owners may be receptive to policies and programs to reduce violence among pediatric populations.